A Legal Analysis of the Application of Strict Liability and the Role of Courts in Civil Litigation for Environmental Pollution - Siti Shanda Radhova; Sigar P. Berutu; Aida Ardini (Al-Adalah: Jurnal Hukum dan Politik Islam, 2026)
The principle of strict liability constitutes a fundamental instrument in environmental law aimed at strengthening accountability for high-risk business activities and ensuring the restoration of environmental damage. In Indonesia, this principle is codified in Article 88 of Law Number 32 of 2009 on Environmental Protection and Management. However, its application in environmental civil litigation continues to encounter significant challenges, particularly following regulatory changes introduced through the Job Creation Law.  This study analyzes the legal framework governing strict liability in Indonesian environmental law, the juridical constraints affecting its implementation in environmental civil lawsuits, and the judicial reasoning reflected in Decision Number 20/Pdt.G/LH/2024/PN Surabaya. The research employs a normative legal research method, utilizing statutory, conceptual, and case approaches.  The findings indicate that the application of strict liability in judicial practice still faces several obstacles, particularly in proving environmental loss and establishing complex causal relationships, as well as the reliance on scientific evidence. Nevertheless, the court’s decision demonstrates a progressive interpretation of strict liability by emphasizing the precautionary principle, the polluter pays principle, and the imperative of environmental restoration.  This study underscores the importance of strengthening regulatory frameworks and developing technical guidelines for environmental damage valuation in order to enhance the effectiveness of strict liability implementation in environmental civil litigation.